The life of the longhouse an archaeology of ethnicity - Metcalf, Peter (Cambridge University Press, 2010)
For two centuries, travellers were amazed at the massive buildings found along the rivers that flow from the mountainous interior of Borneo. They concentrated hundreds of people under one roof, in the middle of empty rainforests. There was no practical necessity for this arrangement, and it remains a mystery. Peter Metcalf provides an answer by showing the historical context, using both oral histories and colonial records.